The Importance of Social Media Creative Content for MSMEs - Siti Paridah Muhtar; Sri Revalina (PT Alahyan Publisher Sukabumi, 2025)
This research aims to describe the importance of creative content on social media for MSMEs. The research method used is descriptive with a qualitative approach. The informants in this study are MSMEs of 20 business actors. The data collection technique uses interview observation and literature study. The data analysis technique uses triangulation which includes data reduction, data presentation, and conclusion drawn. The results of the research are based on several research celebrations. How is your customer involvement in content creation, how many followers you have on social media, how many people see the content you upload, how you respond to the content, how is the reputation of the content you create, states that it is very important for MSMEs to create creative content that is uploaded on social media.